Pengaruh Layanan Rehabilitasi Narkotika terhadap Kualitas Hidup Warga Binaan Pemasyarakatan di Lembaga Pemasyarakatan - Putri Herdriani; Palupi Lindiasari Samputra (Universitas Batanghari Jambi, 2021)
The correctional institution is one of the institutions that provide narcotics rehabilitation services, stipulated in the Regulation of the Minister of Law and Human Rights Number 12 of 2017 concerning the Implementation of Narcotics Rehabilitation Services for Prisoners and Correctional Assistants (WBP). This study aims to analyze the effect of rehabilitation services on prisoners' quality of life in prison at Class II A Narcotics Prison, Jakarta. Researchers used a quantitative approach using the WHOQOL-BREF questionnaire with a total of 493 WBP of secondary data. The data analysis technique used factor analysis and multiple linear regression. The researcher also conducted interviews with two prisoners to see an overview of rehabilitation services that could affect life quality. The results showed a significant and positive influence between psychological health and quality of life of 0.085, social relations with quality of life of 0.114, and a significant favorable influence between physical health and quality of life of 0.045. Meanwhile, the environmental relationship variable does not statistically affect the quality of life. There is a significant simultaneous effect of these four variables on prisoners' quality of life who participate in rehabilitation services at the Class II-A Narcotics Prison, Jakarta.